2018
DOI: 10.1186/s12938-018-0443-2
|View full text |Cite
|
Sign up to set email alerts
|

Co-contraction characteristics of lumbar muscles in patients with lumbar disc herniation during different types of movement

Abstract: BackgroundMuscular performance is an important factor for the mechanical stability of lumbar spine in humans, in which, the co-contraction of lumbar muscles plays a key role. We hypothesized that when executing different daily living motions, the performance of the lumbar muscle co-contraction stabilization mechanism varies between patients with lumbar disc herniation (LDH) and healthy controls. Hence, in this study, co-contraction performance of lumbar muscles between patients with LDH and healthy subjects wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…LDH patients should strengthen muscle activities of the TA and LG, especially the RF, and weaken the muscle activity of the BL by choosing an appropriate rehabilitation training. Our findings are consistent with those of previous studies showing greater co-contraction between antagonistic muscles around the lumbar region of LDH patients and in the lower limb of older adults; additionally, this observation is extended to the lower limb muscles of LDH patients during walking 3,19 . The TA-LG co-contraction increased in LDH patients as an inefficient muscular coordination strategy, which can compensate for pain, numbness, stability, and proprioception caused by prolonged muscle co-contraction or disordered timing of muscle activation in the TA and LG during walking 5,26 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…LDH patients should strengthen muscle activities of the TA and LG, especially the RF, and weaken the muscle activity of the BL by choosing an appropriate rehabilitation training. Our findings are consistent with those of previous studies showing greater co-contraction between antagonistic muscles around the lumbar region of LDH patients and in the lower limb of older adults; additionally, this observation is extended to the lower limb muscles of LDH patients during walking 3,19 . The TA-LG co-contraction increased in LDH patients as an inefficient muscular coordination strategy, which can compensate for pain, numbness, stability, and proprioception caused by prolonged muscle co-contraction or disordered timing of muscle activation in the TA and LG during walking 5,26 .…”
Section: Discussionsupporting
confidence: 93%
“…Older adults showed increased muscle co-contraction of the lower extremity to stiffen joints, in order to compensate for deteriorations in postural control and sensory processing 15 . A previous study showed inadequate muscular coordination of LDH patients considering the greater co-contraction between antagonistic muscles around the lumbar region during backward bending 3 . Although co-contraction reflects the neuromuscular control and coordination between muscles during walking, the lower-limb intermuscular co-contraction during walking in LDH patients has not been reported.…”
mentioning
confidence: 92%
“…9,20 One study evaluated the activation of the stabilizing musculature in different situations, evaluating the neuromuscular activation during eccentric activity, observing that there was an increase in the activation of the antagonist (Transverse Abdominal) during spinal extension compared to the control group. 22 In individuals with acute and subacute low back pain, no change in neuromuscular activation was observed between the groups, suggesting that these changes may be related to the process of pain chronification.…”
Section: Discussionmentioning
confidence: 91%
“…Electroneuromyography was the most widely used method for assessing neuromuscular muscle activation, being used in 8 studies, but no review study was observed for validation of the method. [7][8][9]17,18,20,22,23 Regarding the alterations in neuromuscular activation it was observed that individuals with pain present a delay in the anticipatory neuromuscular activation at the beginning of the movement of the lower limbs, when getting up and during long periods in the sitting position. 7,8,20,23 These situations have been reported as frequent complaints from patients with pain.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar disc herniation (LDH) is a common disease in spine surgery. It is the most common cause of lower back and lower leg pain and it mainly occurs in middleaged and old people [1] . The clinical manifestations of LDH include lumbago and sciatica, as well as pain, numbness and weakness of lower limbs [2] .…”
mentioning
confidence: 99%